Slovensko krava se pomišlja 'krava se goni' - Furlan, Metka (Jezikoslovni zapiski, 2009)
The Slovenian dialect verb pomišljati se 'to be in heat (referring to a cow)' arose through reflexivization of the verb *pomišljati, which meant 'to hunt' in early Slovenian and, like other members of the Slavic world family*mysliti in the sense of 'to hunt / hunter', points to the use of the word family in hunting as a taboo event among the Slavs.
Keywords: etimologija; etymology; leksika; Slavic languages; slovanski jeziki; Slovene; slovenščina